A nomenclatural and taxonomic note on Micrella Punnett, 1901 (Nemertea: Heteronemertea) - Kajihara, Hiroshi (Zootaxa, 2018)
I propose to synonymize the two monotypic heteronemertean genera Micrella Punnett, 1901 and Zygeupolia Thompson, 1900 in light of the morphological similarity between the two, based on available information from literature. My proposal not only results in a new combination, Zygeupolia rufa (Punnett, 1901) comb. nov., but also resolves homonymy of Micrella Punnett, 1901 with the ptiliid coleopteran Micrella Motschulsky, 1868 as well as the heterobranch gastropod Micrella Bergh, 1899.